Advancing RAS/RASopathy therapies: An NCI‐sponsored intramural and extramural collaboration for the study of RASopathies. Issue 4 (8th January 2020) - Gross, Andrea M.; Frone, Megan; Gripp, Karen W.; Gelb, Bruce D.; Schoyer, Lisa; Schill, Lisa; Stronach, Beth; Biesecker, Leslie G.; Esposito, Dominic; Hernandez, Edjay Ralph; Legius, Eric; Loh, Mignon L.; et al.
Abstract: RASopathies caused by germline pathogenic variants in genes that encode RAS pathway proteins. These disorders include neurofibromatosis type 1 (NF1), Noonan syndrome (NS), cardiofaciocutaneous syndrome (CFC), and Costello syndrome (CS), and others. RASopathies are characterized by heterogenous manifestations, including congenital heart disease, failure to thrive, and increased risk of cancers. Previous work led by the NCI Pediatric Oncology Branch has altered the natural course of one of the key manifestations of the RASopathy NF1. Through the conduct of a longitudinal cohort study and early phase clinical trials, the MEK inhibitor selumetinib was identified as the first active therapy for the NF1‐related peripheral nerve sheath tumors called plexiform neurofibromas (PNs). As a result, selumetinib was granted breakthrough therapy designation by the FDA for the treatment of PN. Other RASopathy manifestations may also benefit from RAS targeted therapies. The overall goal of Advancing RAS/RASopathy Therapies (ART), a new NCI initiative, is to develop effective therapies and prevention strategies for the clinical manifestations of the non‐NF1 RASopathies and for tumors characterized by somatic RAS mutations. This report reflects discussions from a February 2019 initiation meeting for this project, which had broad international collaboration from basic and clinical researchers and patient advocates.